If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + -11 = 22 Reorder the terms: -11 + a = 22 Solving -11 + a = 22 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + a = 22 + 11 Combine like terms: -11 + 11 = 0 0 + a = 22 + 11 a = 22 + 11 Combine like terms: 22 + 11 = 33 a = 33 Simplifying a = 33
| 85=6k+3-(2k+5) | | YGAF-YGAF= | | 6|4y-3|-2=16 | | 85=6k+3-(k+5) | | 84=6k+3-(k+2) | | df+2=2f-2d | | 84=6k+3-(k+5) | | 5y+3x-(-2y+2)= | | 625a+b+c=0.5 | | 84=7k+3-(k+5) | | 33+6y=141 | | -3(3+4b)+7=82 | | 625a+25b+c=0.5 | | 8x+5-3x+8=90 | | 4|5y-4|-1=7 | | -3(3+4b)7=82 | | y+6=1.33(x+3) | | 5-3[2x-7(3x-4)]= | | v+4=2v+6 | | Ax+px=w | | y+6=.75(x+3) | | UO+2=2UO | | y-6=-.75(x-3) | | ok+1=145 | | 2ab+6ac-2ya= | | 12=5x+9 | | 19x+4+21x-4=180 | | 21x+3+13x+7=180 | | y-6=.75(x-3) | | 2=5x+4 | | 25-8-3+6-2+5= | | X+6=4-6 |